2021
DOI: 10.1080/25785826.2021.1928383
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictive factors of difficult-to-treat rheumatoid arthritis: the KURAMA cohort

Abstract: Difficult-to-treat rheumatoid arthritis (D2T RA) is a multifactorial condition in which disease activity of RA persists despite consecutive treatment with biological or targeted synthetic disease-modifying antirheumatic drugs (b/tsDMARDs). To evaluate the prevalence and predictive risk factors of D2T RA in our institution, a single-center, retrospective study was conducted. Medical records of RA patients, who visited our hospital from 2011 to 2020 and had a follow-up of more than 6 months, were retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 26 publications
1
19
0
1
Order By: Relevance
“…Therefore, this review must also come with the usual caveat that it might not be generalizable to other institutions with different patient populations and different approaches to management of RA with TTs. However, our result of ∼10% of patients within our cohort having RefRA is comparable to other studies in the area [ 10 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, this review must also come with the usual caveat that it might not be generalizable to other institutions with different patient populations and different approaches to management of RA with TTs. However, our result of ∼10% of patients within our cohort having RefRA is comparable to other studies in the area [ 10 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…Under specific stimuli, circulating monocytes migrate to a specific location in the bones and then fuse with each other to become mature multinucleated osteoclasts (3,4). Current therapies for RA are not effective in all patients, recently several studies reported that approximately 3~10% of RA patients have been estimated as "difficult-to-treat" RA which defined by multiple biologic disease modifying anti rheumatic drugs (bDMARDs)/targeted synthetic DMARDs failure, rapid progressive bone destruction, moderate disease activity despite appropriate treatment and so on (5)(6)(7). Moreover, not all patients can be treated due to the high cost of medication and the occurrence of adverse events such as infection.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the proportion of patients who fulfill the criteria of D2T RA or who show multiple b/tsDMARD resistance in patients with RA has been reported in several cohort studies worldwide, mostly in the 5–20% range ( 15 19 ). In our cohort, 7.9% of 672 patients with RA fulfilled the definition of D2T RA ( 20 ). These results may reflect the widespread use of high-dose MTX and b/tsDMARDs following the treat-to-target strategy, resulting in relatively favorable disease control in 80–90% of patients with RA.…”
Section: Current Status and Unsolved Problems Of Difficult-to-treat Ramentioning
confidence: 98%
“…For example, in our cohort, 21.2% showed moderate to high disease activity at the last visit, with no history of b/tsDMARD use. This population may have included patients with limited access to b/tsDMARDs owing to high costs ( 20 ). In the definition of D2T RA, the following is described in the footnote: failure of ≥ 2 b/tsDMARDs unless restricted by access to treatment due to socioeconomic factors ( 6 ) ( Figure 1 ).…”
Section: Current Status and Unsolved Problems Of Difficult-to-treat Ramentioning
confidence: 99%
See 1 more Smart Citation